Beyond knowledge management : what every leader should know - Liebowitz, Jay , 1957- (CRC Press, 2012)
Although knowledge management (KM) has already helped numerous organizations achieve competitive advantages, many organizations have yet to embark on their knowledge management journey. Geared for executives and senior managers, Beyond Knowledge Management: What Every Leader Should Know is concise and easy-to-read. It looks at 10 areas where organizations can gain competitive advantage. It shows you how to make better decisions, avoid knowledge loss, and maximize the intellectual assets of your organization. Edited by Jay Liebowitz -- who is among the top 10 KM researchers/practitioners worldwide -- the book examines key areas that can add value to your organization. Each chapter opens with an introduction to one of these promising areas, followed by case studies from industry, government, and not-for-profits. The case studies demonstrate how leaders at organizations such as The Coca-Cola Company, e-Bay, PricewaterhouseCoopers, University of Maryland University College, Northrop Grumman, and the U.S. Department of Health and Human Services have used the concepts discussed in the book to improve decision making. The distinguished contributors from these organizations explain how to use information and decision technologies, strategic intelligence, e-learning, human capital, innovation, globalization, and relationships, to improve operations and achieve an advantage over your competitors. The powerful approaches described in this book will not only help you preserve your most valued intellectual assets but also infuse the vitality and creativity your organization will need to stay one step ahead of the competition. -- From publisher summary